PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK MULIA PESERTA DIDIK DI SMAN 5 KENDARI - Herman DM (Institut Agama Islam Negeri Kendari, 2016)
AbstractThis study examines the professionalism of teachers of Islamic education in fostering moral values of students in SMAN 5 Kendari. The results showed that the professionalism of teachers of Islamic education at SMAN 5 Kendari enough to contribute to the formation of a noble character of learners, especially in the school environment. The picture of noble character of students at SMAN 5 Kendari when viewed from the aspect of discipline in following the activities at school, harmony among learners, consistent in performing worship, and mutual help and responsibility in carrying out the tasks assigned by the teacher, has been able to be actualized in in the school environment although most still seem just a mere formality. Professional efforts made by the Islamic Education teachers in fostering the noble character of students at SMAN 5 Kendari is adaly, weekly, and yearly program.Key words: Islamic education, profesionalism of teacher, Islamic moral guidanceAbstrakPenelitian ini mengkaji profesionalisme guru Pendidikan Agama Islam dalam pembinaan akhlak mulia peserta didik di SMAN 5 Kendari. Hasil penelitian ini menunjukkan bahwa profesionalisme guru Pendidikan Agama Islam di SMAN 5 Kendari cukup berkontributif terhadap pembentukan akhlak mulia peserta didik khususnya di lingkungan sekolah. Adapun gambaran akhlak mulia peserta didik di SMAN 5 Kendari apabila ditinjau dari aspek kedisipilinannya dalam mengikuti kegiatan di sekolah, kerukunan antar peserta didik, keistiqamahan dalam melaksanakan ibadah, dan tolong-menolong serta tanggung jawab dalam melaksanakan tugas yang diberikan oleh guru, sudah mampu diaktualisasikan di dalam lingkungan sekolah walaupun sebagian besar masih terkesan sekadar formalitas belaka. Upaya profesional yang dilakukan oleh guru Pendidikan Agama Islam dalam membina akhlak mulia peserta didik di SMAN 5 Kendari yaitu membuat program harian, mingguan, dan tahunan.Kata kunci: Profesionalisme guru, pendidikan Islam, akhlak mulia.